Ucapan Terima Kasih Tim Editor JAL Vo. 5, No. 2, Oktober 2019 - JAL, Pengelola (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019, 2019)
Ucapan Terima Kasih Tim Editor JAL Vo. 5, No. 2, Oktober 2019